Effect of grazing severity on perennial ryegrass herbage production and sward structural characteristics throughout an entire grazing season. (4th April 2013) - Tuñon, G.; Kennedy, E.; Horan, B.; Hennessy, D.; Lopez‐Villalobos, N.; Kemp, P.; Brennan, A.; O'Donovan, M.
Abstract The objective of this study, which was part of a larger grazing‐systems experiment, was to investigate the cumulative impact of three levels of grazing intensity on sward production, utilization and structural characteristics. Pastures were grazed by rotational stocking with Holstein–Friesian dairy cows from 10 February to 18 November 2009. Target post‐grazing heights were 4·5 to 5 cm (high; H), 4 to 4·5 cm (intermediate; I) and 3·5 to 4 cm (low; L). Detailed sward measurement were undertaken on 0·08 of each farmlet area. There were no significant treatment differences in herbage accumulated or in herbage harvested [mean 11·3 and 11·2 t dry matter (DM) ha−1 respectively]. Above the 3·5 cm horizon, H, I and L swards had 0·56, 0·62 and 0·67 of DM as leaf and 0·30, 0·23 and 0·21 of DM as stem respectively. As grazing severity increased, tiller density of grass species other than perennial ryegrass (PRG) decreased (from 3, 350 to 2, 780 and to 1771 tillers m−2 for H, I and L paddocks respectively) and the rejected area decreased (from 0·27 to 0·20 and to 0·10 for H, I and L paddocks respectively). These results indicate the importance of grazing management practice on sward structure and quality and endorse the concept of increased grazing severity as a strategy to maintain high‐quality grass throughout the grazing season. The findings are presented in the context of the need for intensive dairy production systems to provide greater quantities of high‐quality pasture over an extended grazing season, in response to policy changes with the abolition of EU milk quotas.